Animal Friendships / [electronic resource] - Dagg, Anne Innis (Cambridge : Cambridge University Press, 2011)
Research into social behaviour in animals has often focused on aggression, yet members of social species are far more likely to interact with each other in a positive way. Animal Friendships explores non-sexual bonding behaviours in a range of mammalian and avian species. Through analysis of factors which trigger and deepen friendships, Dagg uncovers a world of intricate and complex social interactions. These factors include sources of food, formation of coalitions, playdates for infants, mutual grooming and the apparent pleasure of simple companionship. Chapters cover different types of friendship: from those between two individuals, such as male-female or parent-offspring friendships, to those within family groups and even inter-species friendships. Not only does the book explore how and why friendships form, it also showcases the ingenious field techniques used by researchers enabling the reader to understand the scientific methodology. An invaluable read for both researchers and students studying animal social bonding.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Animal behavior